EVALUASI PEMANFAATAN MEDIA PEMBELAJARAN IPA DALAM MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Nia Kurniasih, Enok; Prasetyono, Hendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the evaluation of science (IPA) learning at the elementary school level based on a literature review approach. Evaluation is an essential component in the learning process as it functions to measure the achievement of learning objectives and improve the quality of teaching and learning activities. The method used in this study is a qualitative approach with a literature study design, which involves collecting, reviewing, and analyzing data from various relevant academic sources such as journals and books. The results of the study indicate that learning evaluation plays a significant role in improving students' learning outcomes and motivation. However, several challenges are still found, such as the dominance of cognitive assessment, limited measurement of affective and psychomotor aspects, and teachers’ lack of ability in designing higher-order thinking skills (HOTS)-based evaluation instruments. In addition, technical and communication barriers, especially during online learning, also affect the effectiveness of evaluation implementation. Therefore, improving teachers’ professional competence in designing and implementing comprehensive and continuous evaluation is necessary to support better learning outcomes. In conclusion, the development of a systematic, holistic, and student-centered evaluation system is crucial to enhance the quality of science learning in elementary schools.